Rancang Bangun Sistem Keselamatan terhadap Gas CO2 dalam Ruang Penyimpanan Tabung Gas CO2 Menggunakan Raspberry Pi Pico W - Ignatius Sudarto Hasugian; Edi Kurniawan; Diyah Purwitasari (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The storage space for CO2 gas cylinders is inside the ship's accommodation, so there is a risk of danger if a leak occurs because the ship's accommodation has poor air circulation. This research is devoted to removing dangerous gases from the room. This research designs and modifies a tool that can detect CO2 levels and can provide a danger signal to the surroundings. This modification uses a Raspberry Pi Pico W microcontroller. This research method uses system design, a series of tools with wiring design and uses 2 test plans, namely: testing static and dynamic testing. Testing the precision of the sensor by reading the CO2 leak detector using a CO2 measuring instrument obtained an average error value of 3.5%. The error value is still categorized as a safe difference value and the prototype works according to the expected function. Testing the function of the tool results in values ​​for the MQ-135 buzzer and exhaust fan sensors which will turn on if the CO2 level is above 600 ppm in accordance with the safe threshold for CO2 levels in the air which has been set in the program. Telegram request bot testing can work well as expected. Testing the Telegram Receive bot can work well as expected. However, for testing Telegram bots, requests and receives are influenced by the internet network.